USE OF GAS PURIFICATION CATALYSTS - Дровнін, С. С. (Proceedings of National Aviation University (archive), 2021)
The use of catalysts made from waste from the electronics and metallurgical industries for the purification of nitrogen-containing gases used in the treatment of mineral oils and hydraulic fluids to improve their performance is proposed.